Calibration of thermographic spot weld testing with X-ray computed tomography. Issue 1 (2nd January 2017) - Myrach, Philipp; Jonietz, Florian; Meinel, Dietmar; Suwala, Hubert; Ziegler, Mathias
Abstract: The paper presents an attempt for the calibration of an active thermography method that is suitable for the non-destructive evaluation of spot welds. Nowadays, the quality of spot welds is commonly characterised by the application of random chisel tests, which are time consuming, expensive and destructive. Recently a non-destructive testing method by means of active thermography was proposed that relies on the fact that the mechanical connection formed by the spot weld also serves as a thermal bridge between the two steel sheets joined in the welding process. It is shown in this paper that this thermal bridge can be thermographically characterised by extracting a measure for the spot weld diameter and hence the quality of the spot weld. The determination of the absolute value of the diameter hereby relies on a calibration of the testing system, which is performed by means of X-ray computed tomography in this study. The experiments were carried out using different experimental approaches, namely transmission as well as reflection geometry wSetup in reflectionith laser illumination. A comprehensive evaluation of samples produced using different welding currents, hence different quality, was carried out in order to validate the thermographic results.